Weight-Loss Program Assistance System for Obesity Patients Based on Internet of Things (IoT) Technology - I Gusti Bagus Astawa; I Ketut Agung Enriko (Ultimatics : Jurnal Teknik Informatika, 2016)
These days, the use of Internet technology can be found in almost every sector of human life. One of the advanced Internet technologies is Internet of Things (IoT), that is a technology where devices can communicate via Internet connectivity. It is used in many vital industries like automotive, electricity, home automation, and healthcare. This study aims to implement IoT technology for healthcare sector, i.e. in helping obesity people to pursue their weight-loss program (WLP). The result is a system which consists of a smart weight scale, a mobile application, and food menu recommendation database in order to help obesity people in their WLP program. A trial to some obesity patients is performed to collect data. Index Terms—Internet of things; overweight; weight loss program; food recommendation